Role and Significance of Markers of Inflammation in the Asthmatic Disease - Goseva, Zlatica; Jovanovska Janeva, Elena; Gjorcev, Angelko; Arsovski, Zoran; Pejkovska, Sava (ID Design 2012/Scientific Foundation SPIROSKI, 2015)
BACKGROUND: Asthma is characterized by airway inflammation which can be reversible. AIM: Investigation the importance of eosinophils, ECP and IL-5 in asthmatics versus patients with obstructive bronchitis and healthy subjects. We investigated the values before and after the treatment in asthmatics. MATERIAL AND METHODS: We studied 77 subjects divided in three groups as follows: 1) asthma patients; 2) patients with obstructive bronchitis and 3) control group of healthy subjects. In all the subjects there were determined: Total number of eosinophils (Eo), eosinophilic cationic protein (ECP), Interleukin 5 (IL-5) and allergy tests. RESULTS: The total number of eosinophils was significantly increased in the group of asthma patients versus second and third group. We found that the presence of ECP demonstrate an ongoing inflammation, with or without clinical symptoms of asthma patients. There was significant difference between the values of ECP of asthma patients versus second and third group. Our results have shown that IL-5 was significantly increased versus second group and controls (p < 0.01). We also found the decrease of the values of inflammatory markers after the treatment with corticosteroids. CONCLUSIONS: Eosinophils, ECP and IL-5 could be useful markers for selecting allergic patients and could be the monitors of treatment effects
Keywords: asthma; markers; inflammation; eosinophil; eosinophil cationic protein; IL-5